2022
DOI: 10.1111/acfi.13040
|View full text |Cite
|
Sign up to set email alerts
|

Impact of product market competition on real activity manipulation: Moderating role of managerial ability

Abstract: In this study, we examine whether managerial ability moderates the association between product market competition and real earnings management. Prior literature largely supports the disciplinary effect of competition, suggesting that competition reduces real activity manipulation. We argue that this association is different depending on the level of managerial ability. Based on the reputation hypothesis, we argue that able managers negatively moderate the association between competition and real activity manip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Industry competition is significant variable affecting the boards' compensation decisions and CEO turnover. Researchers have shown that firm performance is influenced by market structure, and changes in other structural factors such as market competition, growth, and barriers to professional mobility (e.g., Biswas et al, 2022; Jung & Yoo, 2022; Shi et al, 2018; Short et al, 2007). Clearly, the intensity of market competition affects a company's profitability and CEO performance, which, in turn, determines a CEO's compensation and job security.…”
Section: Introductionmentioning
confidence: 99%
“…Industry competition is significant variable affecting the boards' compensation decisions and CEO turnover. Researchers have shown that firm performance is influenced by market structure, and changes in other structural factors such as market competition, growth, and barriers to professional mobility (e.g., Biswas et al, 2022; Jung & Yoo, 2022; Shi et al, 2018; Short et al, 2007). Clearly, the intensity of market competition affects a company's profitability and CEO performance, which, in turn, determines a CEO's compensation and job security.…”
Section: Introductionmentioning
confidence: 99%